Practical robust control using Self-regulation Nonlinear PID controller for pneumatic positioning system - Sy Najib Sy Salim; M. F. Rahmat; N. H. Sunar; A. A. M. Faudzi; Z. H. Ismail; Shamsul Anuar Samsudin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper investigates the robustness of the pneumatic positioning system controlled by Self-regulation Nonlinear PID (SNPID) controller. This controller is executed by utilizing the characteristic of rate variation of the nonlinear gain that are readily available in Nonlinear PID (NPID) controller. A Self-regulation Nonlinear Function (SNF) is used to reprocess the error signal with the purpose to generate the value of the rate variation, continuously. Simulation and experimental tests are conducted. The controller is implemented to a variably loads and pressures. The comparison with the other existing method i.e. NPID and conventional PID are performed and evaluated. The effectiveness of SNPID + Dead Zone Compensator (DZC) has been successfully demonstrated and proved through simulation and experimental studies